Research of the Influence of Supporting Method on the Statics Characteristic of Large Wind Turbine Gearbox - Ji Kefeng; Zhang Shijie (Jixie chuandong)
Due to the large size and weight of large wind turbine gearbox,its statics characteristic and gear contact characteristic are different under different supporting method. Taking the large wind turbine gearbox as research object,based on the performance parameters under the ultimate load,the influence of the different supporting method on wind turbine gearbox is researched by using the finite element method（ FEM）,and the contrastive analysis of calculation results is carried out. The results show that the stress and deformation of the box are much smaller if there is a foot supporting at the bottom of the gear box than that if there is no foot supporting,the gear contact stress of the gearbox changes little,and the meshing misalignment of the first-stage gear transmission varies greatly. The research results provide a data basis for the optimal design of large wind turbine gearbox.